SAVINGS OF CITIZENS AS A SOURCE OF DEVELOPMENT OF NON-STATE PENSION PROVISION IN RUSSIA - Y. Indychenko; G. Fatkhlislamova (Вестник университета)
The role of population savings in the development of voluntary pension provision in the Russian conditions has been investigated. The results of a study of the dynamics of savings of citizens, deposits of individuals in credit institutions, insurance premiums for pension provision and insurance reserves of non-state pension funds for the period from 2005 to 2017 are presented. The nature of the population’s saving behavior has been revealed, as well as the role of non-state sources of financing voluntary pension insurance. The key problems of attracting sources of financing of the system of non-state pension provision are identified.